ANALISIS KELAYAKAN OBJEK WISATA HUTAN MANGROVE GURAPING DI KECAMATAN OBA UTARA, KOTA TIDORE KEPULAUAN, PROVINSI MALUKU UTARA - Latupapua, Yosevita Th; Soselisa, Fanny (Departement of Aquatic Resources Management, Fisheries and Marine Science Faculty, Pattimura University, 2022)
Guraping mangrove tourism object is located in North Oba District, Tidore Island City. An area that has an important role in supporting physical, chemical, biological, and social functions. However, with the increase in population, it will certainly affect the ecological sustainability of the mangrove itself due to logging actions carried out by the community. Therefore, in supporting the preservation of mangroves in the village of Guraping, the mangrove area is designated as a protected area and a natural tourist attraction. To support the management of natural tourism in the mangrove area, it is necessary to be supported by information on the feasibility of the Guraping mangrove tourism object. The purpose of this study is to analyze the feasibility of the Guraping mangrove tourism object for natural tourism activities. The research was conducted in July 2022. The research method used is descriptive quantitatif method. Determination of sample points using the purposive sample method, sampling was carried out at 3 observation stations, data analysis using quantitative analysis of mangrove feasibility. The results showed that the mangroves of the Guraping tourism area had an IKW value of 72 with the S2 category (